Design and Fabrication of a Tip‐Like ZnO Nanotube Array Structure with Condensate Microdrop Self‐Propelling Function. Issue 11 (16th August 2016) - Luo, Yuting; Gong, Xiaojing; Chen, Ying; Zhu, Jie; Wei, Jiandong; Gao, Xuefeng
Abstract: Here, we present a type of tip‐like nanotube array with condensate microdrop self‐propelling (CMDSP) function. Based on the basic principle that condensate microdrops can self‐remove via coalescence‐released weak surface energy as long as interface adhesion induced energy dissipation is sufficiently low, we design tip‐like nanotubes with extremely low solid–liquid interface adhesion. To verify the feasibility of this idea, we propose a strategy of preferential etching of six corners and the interior of ZnO nanopencils to achieve tip‐like nanotubes. Our studies demonstrate that this nanostructure can be achieved by immersing ZnO nanopencils in 0.006 m HCl aqueous solution at 80 °C for 3 h. After silane modification, the resulting nanostructure shows CMDSP function. This work offers a new avenue for developing CMDSP functional films, which can find a variety of technological applications such as moisture self‐cleaning, antifrosting and enhancing heat transfer. Abstract : Novel tip‐like nanotube structures with condensate microdrop self‐propelling (CMDSP) function are designed and verified based on controllable growth of arrays of tip‐like ZnO nanotubes, which can be realized by a strategy of skillfully utilizing preferential etching of the six corners and inner part of ZnO nanopencils. This work offers a new avenue for developing CMDSP functional films and other functional nanomaterials.